Losing Items in the Psychogeriatric Nursing Home: The Perspective of Residents and Their Informal Caregivers - van Hoof, J. (Gerontol Geriatr Med, 2016)
Introduction: Losing items is a time-consuming occurrence in nursing homes that is ill described. An explorative study was conducted to investigate which items got lost by nursing home residents, and how this affects the residents and family caregivers. Method: Semi-structured interviews and card sorting tasks were conducted with 12 residents with early-stage dementia and 12 family caregivers. Thematic analysis was applied to the outcomes of the sessions. Results: The participants stated that numerous personal items and assistive devices get lost in the nursing home environment, which had various emotional, practical, and financial implications. Significant amounts of time are spent on trying to find items, varying from 1 hr up to a couple of weeks. Numerous potential solutions were identified by the interviewees. Discussion: Losing items often goes together with limitations to the participation of residents. Many family caregivers are reluctant to replace lost items, as these items may get lost again.